Managing with passion : making the most of your job and your life - Ginsburg, Sigmund G. (New York : Wiley, 1996)
"Drawing upon his thirty years as a senior manager and management consultant, Sigmund G. Ginsburg provides ninety practical lessons designed to help you achieve the highest levels of personal and professional accomplishment and success while nurturing excellence in your company and co-workers." "Ginsburg provides proven concepts, suggestions, guidelines, ploys, and counterploys that help you to improve and enhance your management style and hone your management skills. He also delves into a wide range of essential ethical issues and provides a set of cogent rules that will be of inestimable value to anyone concerned with the problem of how to be a good person and an excellent manager at the same time."--BOOK JACKET.
Includes index.
Keywords: Management; Organizational behavior; Management; Organizational behavior